Shiver trilogy. 2, Linger - Stiefvater, Maggie, 1981- (New York : Scholastic Press, 2010)
"As Grace hides the vast depth of her love for Sam from her parents and Sam struggles to release his werewolf past and claim a human future, a new wolf named Cole wins Isabel's heart but his own past threatens to destroy the whole pack."
Keywords: Love -- Fiction; Wolves -- Fiction; Human-animal relationships -- Fiction; Metamorphosis -- Fiction; Supernatural -- Fiction